Correlation and regression analysis of unionised ammonia ions, NH3 and pH in ornamental fish aquatic environment / Fatin Izyani Mohamad Robi ... [et al.] - Mohamad Robi, Fatin Izyani; Ahmad, Mohamad Naim; Mohd Zain, Nur Syafiqah Nadiah; Sulaiman, Mohd Suhaimi; Ishak, Khairul Anuar; Abd Rahman, Mohamad Faizal (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
Assessing ammonia in water is very important for fish farmers as it is one of the pollutants that may affect the water quality. In water, ammonia can be found either in the form of unionised ammonia (NH3) or ionised ammonia (NH4+), which contribute to a total ammonia nitrogen (TAN). In assessing the ammonia toxicity, NH3 provides a more accurate measure of toxicity and needs to be monitored consistently, rather than relying solely on TAN. However, the method of measuring NH3 in water can be complex and challenging. Therefore, the ability to determine the correlation between NH3 and other parameter which is easier to be measured (such as pH) is crucial to enable the estimation of NH3. This study was conducted to determine the correlation between NH3 and pH based on the data collected from Redgold Aquatics ornamental fishponds located in Sik, Kedah. The pH was assessed by a commercial measuring device, while the NH3 was calculated using an appropriate mathematical equation that requires the data of pH, TAN, and temperature. The correlation and regression analysis were conducted via the IBM SPSS tool and Microsoft Excel. The result shows that NH3 and pH are highly correlated with regression equation of NH3 = 0.01pH – 0.07. In addition, factors that may affect the total ammonia value have been discussed thoroughly in this work. The analysis of these water quality parameters may assist farmers in estimating the toxic ammonia, NH3 from the known water pH.